Opinion formation process in a hierarchical society - Romero Longar, Maria Celeste (2025)
In this work we study the formation of consensus in a hierarchicalpopulation. We derive the corresponding kinetic equations,and analyze the long time behaviour of their solutions for the case offinite number of hierarchical levels, obtaining explicit formula for theconsensus opinion.